2010
DOI: 10.2298/vsp1005369m
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Lyme disease development after a tick bite

Abstract: In prevention of Lyme disease it is important to urgent remove a tick, to use a correct procedure of removing and to remove the whole tick without any remnants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…The ticks were professionally removed, and none of the soldiers in our study gave accurate information on how long the ticks remained in the skin. The results of Mladenovic et al (2010) showed that subjects in which ticks remained in the skin for less than 24 hours did not develop EM, indicating that removal of a tick within this period may have a protective effect. However, if a tick remains attached longer, the risk of developing B. burgdorferi infection increases proportionally ( Mladenovic et al , 2010 ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The ticks were professionally removed, and none of the soldiers in our study gave accurate information on how long the ticks remained in the skin. The results of Mladenovic et al (2010) showed that subjects in which ticks remained in the skin for less than 24 hours did not develop EM, indicating that removal of a tick within this period may have a protective effect. However, if a tick remains attached longer, the risk of developing B. burgdorferi infection increases proportionally ( Mladenovic et al , 2010 ).…”
Section: Discussionmentioning
confidence: 97%
“…The results of Mladenovic et al (2010) showed that subjects in which ticks remained in the skin for less than 24 hours did not develop EM, indicating that removal of a tick within this period may have a protective effect. However, if a tick remains attached longer, the risk of developing B. burgdorferi infection increases proportionally ( Mladenovic et al , 2010 ). Some authors found though that migration of spirochetes in ticks and their transmission to susceptible hosts was recorded in less than 24 hours after a tick bite ( Kahl et al , 1998 ; Crippa et al , 2002 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…No sul dos EUA existe uma apresentação conhecida como doença de Masters ou STARI (Southern Tick Associated Rash Illness) (Masters et al, 1998), caracterizada pelo desenvolvimento de "rash" semelhante ao EM, na ausência de sintomatologia sistêmica, sendo transmitida pelo Amblyomma americanum e causada pela B. lonestari, a qual é incultivável em meio BSK e, recentemente tornou-se cultivável em células de carrapatos (Varela et al, 2004 (Spach et al, 1993;LoGiudice et al, 2003;Mladenović et al, 2010;Hamer et al, 2010).…”
Section: Doença De Lymeunclassified